A Review of Grass Carp and Related Species Literature on Diet, Behavior, Toxicology, and Physiology Focused on Informing Development of Controls for Invasive Grass Carp Populations in North America - Mark L. Wildhaber; Benjamin M. West; Karlie K. Ditter; Adrian P. Moore; Alex S. Peterson (Fishes, 2023)
Grass carp (Ctenopharyngodon idella) are globally important in aquaculture and aquatic vegetation control. However, escaped grass carp have established invasive populations. A targeted keyword search was performed on a carp (order: Cypriniformes) literature database maintained by the U.S. Geological Survey to identify literature relevant to grass carp. Additional sources cited in reviewed documents and provided by numerous reviewers were also included. There were three focus areas designed to provide support for invasive grass carp management: (1) diet and behavior; (2) physiological constraints, toxicity, and biology; and (3) gut physiology. Each focus area provides information to guide development of potential pathways for invasive grass carp control. Information from other carp species was used to fill in gaps where grass carp information was lacking and provide additional, potential research directions. Diet-related information included food selection and aquacultural diet formulations. Behavioral information included stimuli and non-physical barriers to attract, repel, or stop movement. Physiological constraints, toxicology, reproductive control, and biological control provide a research review for control options. Gut physiology and related control pathways provide knowledge to improve toxin or pathogen delivery. This review provides a basis for developing approaches and research for controlling invasive grass carp populations, aquaculture, and native population management.